2015
DOI: 10.1515/aoas-2015-0002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Caponization on Meat Quality of Greenleg Partridge Cockerels

Abstract: the objective of the study was to determine the effect of caponizing Greenleg partridge cockerels on slaughter parameters and meat quality. in total 80 Greenleg partridge cockerels were assigned to two groups with 40 birds per group. Group i (control) consisted of uncastrated cockerels and group ii contained birds that were castrated at 8 weeks of age. Birds were kept until 24 weeks of age and fed the same diet ad libitum. Body weight was recorded at 1, 8, 16 and 24 weeks of age. dressing percentage, proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 28 publications
5
28
1
5
Order By: Relevance
“…Breast meat capon showed greater CP content and IMF, in comparison with roosters, but no differences were found for moisture, myoglobin, ash and collagen contents in contradiction with Miguel et al (2008), Sirri et al (2009) and Volk et al (2011) that have reported that caponisation had no effect on moisture and CP contents. Miguel et al (2008) and Calik et al (2015) indicated no differences between sexes for ash content, whereas Sirri et al (2009) registered that caponisation increased its content, which was also found in the present work. Lin and Hsu (2013) shown that moisture and ash contents were lower in capon (caponised with 10 weeks) of native Taiwan Country chicken with 28 weeks of age.…”
Section: Meat Physical and Chemical Characteristicssupporting
confidence: 87%
See 4 more Smart Citations
“…Breast meat capon showed greater CP content and IMF, in comparison with roosters, but no differences were found for moisture, myoglobin, ash and collagen contents in contradiction with Miguel et al (2008), Sirri et al (2009) and Volk et al (2011) that have reported that caponisation had no effect on moisture and CP contents. Miguel et al (2008) and Calik et al (2015) indicated no differences between sexes for ash content, whereas Sirri et al (2009) registered that caponisation increased its content, which was also found in the present work. Lin and Hsu (2013) shown that moisture and ash contents were lower in capon (caponised with 10 weeks) of native Taiwan Country chicken with 28 weeks of age.…”
Section: Meat Physical and Chemical Characteristicssupporting
confidence: 87%
“…Miguel et al (2008) and Symeon et al (2010) in capons with 29 weeks (caponisation 8 weeks) and 18 to 24 weeks (early caponisation 3 weeks), respectively, reported that caponisation had no effects on pH and WHC. There were no sex differences for texture, confirming the results obtained by Symeon et al (2010) and Calik et al (2015) in capons with 18 and 24 weeks of age, respectively. However, Sirri et al (2009), Symeon et al (2010 and Lin et al (2011), observed that caponisation decreases texture values in capons with 180 days, 24 and 28 weeks of age, respectively.…”
Section: Meat Physical and Chemical Characteristicssupporting
confidence: 86%
See 3 more Smart Citations